A crítica ao poder em textos líricos dos séculos XIII, XVII e XX: um enfoque sistêmico-funcional - Oliveira, Ulisses Tadeu Vaz de (2014)
The objective of this critical research is the identification of the persuasive strategies that authors from different times used to criticize power holders in their respective contexts. Therefore, the present research aims to conduct a multifunctional study in the theoretical-methodological perspective of the Systemic- Functional Grammar (SFG) of literary productions from three distinct eras, but similar in the relationship of the authors with the existing power and target of their criticisms, namely: (a) satirical chants of Gil Pérez Conde (thirteenth century); (b) poems of Gregorio de Matos Guerra (seventeenth century); and (c) songs of Chico Buarque de Holanda (twentieth century). The analysis of these productions is based on the SFG proposals. It considers the clause as a social event, for which the structure serves to woven together three concurrent types of meanings, or metafunctions: Ideational (refers to information), Interpersonal (refers to the interaction between the producer and the receiver involved in the linguistic process) and Textual (refers to the text construction according to the requirements of the socio-historical-cultural environment). The SFG involves not only the Critical Linguistics, which is an approach that tries to match a textual linguistic analysis method with a social language theory in political and ideological processes, but also the Modality and Appraisal a theoretical extension of the Interpersonal metafunction that blends the author`s positioning with the message content. In this confrontation against the authorities, Appraisal works alongside of the care authors show redressing of affronts to face posed by face-threatening, or politeness. The research aims to answer the following questions: (a) How is power criticism made in the chosen different times? (b) What lexicogrammatical choices were made to criticize in terms of the Ideational and Interpersonal metafunctions? (c) What did rhetorical elements build the persuasion in this process? The results show that the dialogism of the texts points out to the use of similar persuasive structures that identify a satirical genre subcategory, which aggregates texts due to the repression context wrapping them. On the other hand, differences in the persuasive strategies, identified through the analysis, present the uniqueness of the texts and their authors